2017
DOI: 10.18203/2394-6040.ijcmph20170772
|View full text |Cite
|
Sign up to set email alerts
|

A study on waiting time and out-patient satisfaction at Gujarat medical education research society hospital, Valsad, Gujarat, India

Abstract: Background: Gujarat Medical Education Research society started GMERS medical college and tertiary care Hospital in Valsad since last 4 years. As civil Hospital is converted in to tertiary care hospital and many of the departments running in different buildings so, searching the concern OPDs is difficult for patients, waiting time and patients satisfaction is important to avail the services. Patient satisfaction is one of the important goals of any health system, but it is difficult to measure the satisfaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
0
17
0
2
Order By: Relevance
“…Many reviewed literatures on quality of healthcare show that waiting time is one of the most important indicators or variables of healthcare quality. One of such is a cross sectional observational study by the Patels (2017) on waiting time and outpatient satisfaction at Gujarat medical education research society hospital India, using 135patients from the outpatient department (OPD) [13]. A cross sectional survey of nurses (33,659) and patients (11,318) in 12 countries in Europe and the United States on patient safety, satisfaction and quality of hospital care, using hierarchical modelling and robust logistic regression, showed that deficits in hospital care quality were common in all countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many reviewed literatures on quality of healthcare show that waiting time is one of the most important indicators or variables of healthcare quality. One of such is a cross sectional observational study by the Patels (2017) on waiting time and outpatient satisfaction at Gujarat medical education research society hospital India, using 135patients from the outpatient department (OPD) [13]. A cross sectional survey of nurses (33,659) and patients (11,318) in 12 countries in Europe and the United States on patient safety, satisfaction and quality of hospital care, using hierarchical modelling and robust logistic regression, showed that deficits in hospital care quality were common in all countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many reviewed literature on quality of healthcare show that waiting time is one of the most important indicators or variables of healthcare quality. One of such is a cross sectional observational study by the Patels (2017) on waiting time and outpatient satisfaction at Gujarat medical education research society hospital India, using 135patients from the outpatient department (OPD) [13]. A cross sectional survey of nurses (33,659) and patients (11,318)…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, previous studies show that the majority of outpatients wait as long as 80-180 minutes or more in the OPDs, and the commonest reason for this long waiting time is the large number of patients as against few health workers [17,26]. A study in India obtained average waiting time outside the various OPDs of only 12 minutes and 98.52% of patients were very satisfied with it [13]. The finding that very educated patients, unlike the illiterate ones, are less satisfied with waiting time, could be a reflection of their increased awareness of their rights and privileges because of their level of education and therefore more discerning of the expected quality of healthcare services.…”
Section: Discussionmentioning
confidence: 99%